Desenvolvimento da microscopia de força química usando modelagem molecular - Amarante, Adriano Moraes (2013)
In this work was developed a prototype of a new nanobiosensor with molecular specificity through a study of theoretical models of Chemical Force Microscope. For the sensing were used molecular modeling techniques as well as experimental models of the functionalized Atomic Force Microscope tip with the Acetil co-A Carboxylase (ACC) attached. Specific and non-specific inhibitors were used to evaluate substrate-enzyme interactions. The nanobiosensor investigates specific enzymatic inhibition characteristics of the ACC enzyme through the herbicide Diclofop by reversing this process applying a force in a determined direction. The force is theoretically calculated by using molecular dynamic techniques associated to the adhesion force experimentally obtained. Theoretical and experimental questions involving nanobiosensors of AFM tips still obscure until now, such as, the number of functional enzymes attached on the AFM tip, the number of the active sites available to interact after immobilization process, the consequences of the enzyme immobilization as well as the substrate and theoretical adhesion between AFM tip and substrate were analyzed here.